The fiscal implications of the low-carbon transition - Elgouacem, Assia (OECD Green Growth Papers, 2020)
Fossil fuels play an important role in the budget of several governments. On the one hand, half of the countries identified as resource-rich derived 50% or more of their government revenue from fossil-fuel resources. On the other hand, fossil fuel consumption in road transport is an important tax base for several countries. This fiscal entanglement creates specific challenges for countries in preparing for a low carbon future. In addition to the traditional challenges of volatility and unpredictability of resource revenues, resource-rich countries are increasingly exposed to the risk of stranded assets. While energy demand is estimated to grow under current and announced policies, a dramatic reshuffle in the world energy mix will need to take place. In this context, this paper reviews the evidence on the role of fossil fuels in government budget (section 2) and the best practice for the management of resource revenues, including the role of sovereign wealth funds and strategic investment funds (section 3). Section 4 discusses the role of green tax reform in preparing the tax system for the low-carbon transition